2009
DOI: 10.1073/pnas.0911093106
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous internal gene duplication and intron creation in eukaryotes

Abstract: Duplication of genomic segments provides a primary resource for the origin of evolutionary novelties. However, most previous studies have focused on duplications of complete protein-coding genes, whereas little is known about the significance of duplication segments that are entirely internal to genes. Our examination of six fully sequenced genomes reveals that internal duplications of gene segments occur at a high frequency (0.001-0.013 duplications/gene per million years), similar to that of complete gene du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…Another mechanism that is related to the exon intronization model also suffers from the fact that size changes of the encoded proteins ensue. Duplication of intragenic segments (encompassing intronic and flanking exon sequences) may lead to activation of latent splice sites [42], thus creating novel introns or exons (that are flanked by novel introns). Dissenting from the Rogers [39] model, here the splice signals of novel introns reside in dispersed, complex repeats rather than in expanded AGGT repetitions.…”
Section: (1) Intron Generation Via Transposon Insertionmentioning
confidence: 99%
“…Another mechanism that is related to the exon intronization model also suffers from the fact that size changes of the encoded proteins ensue. Duplication of intragenic segments (encompassing intronic and flanking exon sequences) may lead to activation of latent splice sites [42], thus creating novel introns or exons (that are flanked by novel introns). Dissenting from the Rogers [39] model, here the splice signals of novel introns reside in dispersed, complex repeats rather than in expanded AGGT repetitions.…”
Section: (1) Intron Generation Via Transposon Insertionmentioning
confidence: 99%
“…This result is in stark contrast to the comparative studies of their highly conserved orthologous genes, which found very few or no intron gains at all (Coulombe-Huntington & Majewski 2007;Fawcett et al 2012;Roy et al 2003;Yang et al 2013). Considering the high frequency of internal gene duplications, which is 0.0010.013 duplications/gene per million years (Gao & Lynch 2009), it can be stated that intron gain by segmental duplication may be an important force shaping the eukaryotic gene structure.…”
Section: Resultsmentioning
(Expert classified)
“…Due to this methodology, the frequency of intron gain by segmental duplication might have been underestimated previously. To be consistent with this idea, a study that specifically explored intron gains by segmental duplications revealed tens of new introns in humans, mice, and A. thaliana (Gao & Lynch 2009). This result is in stark contrast to the comparative studies of their highly conserved orthologous genes, which found very few or no intron gains at all (Coulombe-Huntington & Majewski 2007;Fawcett et al 2012;Roy et al 2003;Yang et al 2013).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations